PEMANFAATAN TEKNOLOGI MACHINE LEARNING DALAM PERENCANAAN DAN REHABILITASI RUMAH LAYAK HUNI: PERSPEKTIF ARSITEKTUR - Rosyd Rosyadi; Ari wibowo wibowo; Susanto (Jurnal Arsitektur ARCADE, 2025)
Abstract: This study discusses the application of machine learning, specifically the XGBoost model, in the selection and rehabilitation of uninhabitable houses (RTLH) from an architectural perspective. The RTLH rehabilitation program aims to improve housing quality for low-income communities, yet the main challenge is determining which houses require rehabilitation in an objective and efficient manner. By utilizing machine learning algorithms, this research analyzes architectural and socio-economic factors such as structural conditions, spatial layout, building materials, number of occupants, and economic well-being. This model enables a more accurate selection of aid recipients, reduces subjectivity, and enhances program effectiveness. From an architectural perspective, this study emphasizes the importance of ergonomic house design, natural ventilation, energy efficiency, and the use of sustainable materials. The results show that the XGBoost model provides accurate predictions for housing rehabilitation, supports data-driven decision-making, and can be integrated with GIS technology for mapping uninhabitable houses. This technological integration supports the development of adaptive architecture tailored to the needs of residents and environmental conditions. Keyword: Architecture, RTLH, Housing Planning, Machine learning, XGBoost Abstrak: Penelitian ini membahas penerapan machine learning, khususnya model XGBoost, dalam seleksi dan rehabilitasi rumah tidak layak huni (RTLH) dengan pendekatan arsitektural. Program rehabilitasi RTLH bertujuan meningkatkan kualitas hunian bagi masyarakat berpenghasilan rendah, namun tantangan utama adalah menentukan rumah yang paling membutuhkan rehabilitasi secara objektif dan efisien. Dengan memanfaatkan algoritma machine learning, penelitian ini menganalisis faktor arsitektural dan sosial-ekonomi, seperti kondisi struktural, tata letak ruang, material bangunan, jumlah penghuni, serta kesejahteraan ekonomi. Model ini memungkinkan seleksi penerima bantuan secara lebih akurat, mengurangi subjektivitas, dan meningkatkan efektivitas program. Dari aspek arsitektur, penelitian ini menekankan pentingnya desain rumah ergonomis, ventilasi alami, efisiensi energi, dan penggunaan material yang berkelanjutan. Hasil penelitian menunjukkan bahwa model XGBoost memberikan prediksi akurat dalam rehabilitasi rumah, mendukung pengambilan keputusan berbasis data, serta dapat dikombinasikan dengan teknologi GIS untuk pemetaan rumah tidak layak huni. Integrasi teknologi ini mendukung pengembangan arsitektur yang adaptif terhadap kebutuhan penghuni dan kondisi lingkungan. Kata Kunci: Arsitektur, RTLH, Perencanaan Rumah, Machine learning, XGBoost.